Hubungan Kualitas Hidup dengan HbA1c Pasien Pengguna Antidiabetes Oral di RSUD Bandung Kiwari - 10060321013, Lutfi Anggita; Fetri Lestari; Bambang Tri Laksono (Bandung Conference Series: Pharmacy, 2025)
Abstract. Type 2 diabetes mellitus (T2DM) is a progressive chronic disease that requires long-term Oral Antidiabetic Drugs (OAD) therapy which impacts quality of life. Decreased quality of life in T2DM patients is often associated with uncontrolled HbA1c levels. This study aims to analyze the relationship between the quality of life of patients using oral antidiabetic drugs and HbA1c levels. This study was conducted at Bandung Kiwari Hospital during April 2025 using an analytical observational approach based on cross-sectional method. Data were collected through the Diabetes Quality of Life Brief Clinical Inventory (DQoL-BCI) questionnaire, which evaluates the physical, psychological, and social and environmental health aspects of T2DM patients. HbA1c levels were known through medical records. The results showed that patients' quality of life was poor with an average score of 52.50. And there is no significant relationship between the quality of life of T2DM patients using oral antidiabetic drugs with HbA1c levels statistically with a p-value> 0.05. Abstrak. Diabetes melitus tipe 2 (DMT2) adalah penyakit kronis progresif yang memerlukan terapi Oral Antidiabetic Drugs (OAD) jangka panjang yang berdampak pada kualitas hidup. Penurunan kualitas hidup pasien DMT2 sering kali dihubungkan dengan kadar HbA1c yang tidak terkendali. Penelitian ini bertujuan untuk menganalisis hubungan kualitas hidup pasien pengguna antidiabetes oral dengan kadar HbA1c. Studi ini dilakukan di RSUD Bandung Kiwari selama periode April 2025 menggunakan pendekatan observasional analitik berbasis metode cross-sectional. Data dikumpulkan melalui kuesioner Diabetes Quality of Life Brief Clinical Inventory (DQoL-BCI), yang mengevaluasi aspek kesehatan fisik, psikologis, serta hubungan sosial dan lingkungan pasien DMT2. Kadar HbA1c diketahui melalui rekam medis. Hasil penelitian menunjukkan kualitas hidup pasien cukup buruk dengan skor rata-rata 52,50. Serta tidak terdapat hubungan yang signifikan antara kualitas hidup pasien DMT2 pengguna obat antidiabetes oral dengan kadar HbA1c secara statistik dengan nilai p-value >0,05.